Drivers of Donations: Does Religiosity Make a Difference? - Abreu, M. E.; Laureano, Raul M. S.; Vinhas da Silva, Rui; Pedro Dionísio (SSRN, 2014)
The topic of donations is one of high relevance and widely covered in the marketing literature today, being of interest to theoreticians and practitioners alike, particularly due to its implicit links to fundraising research and activities. The reality of what makes a donor ultimately part with his money and give it away to a not for profit organization is a hot contemporary topic. This study looks into religiosity and its moderating impact on the intention for donating to a nonprofit organization. It also compares and contrasts three types of donors: religious, religious but non church goer and secular, highlighting their differences and similarities insofar as donations are concerned. The results show unequivocally that religiosity has the potential to influence donating behavior. Moreover, this study predicts that volunteerism and religious affiliation remain important drivers of donations. The findings are useful for marketers who want to attract and retain donors.